Semiotic Analysis in the Film Barbie (2023): Representation of Patriarchal Culture - Della Setya Anggraini; Sugeng Harianto; Refti Handini Listyani (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The research aims to meticulously explore and analyze the manifestation of patriarchal culture depicted in the film